Empowerment of Msmes by Optimizing Marketing of Local Products in Muntuk Hamlet with Digital Marketing - Iswanto Suwarno; Robbi Rahim; Mohammad Aljanabi; Muhammad Ahmad Baballe; Omar Tanane; Irfan Ahmad; Erwin L. Rimban (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Muntuk Village is located in Dlingo District, Bantul Regency, Special Region of Yogyakarta. Muntuk Village is located in the east of Bantul City. Meanwhile, most of the residents of Dusun Muntuk work as day laborers, farmers, gardeners, wood and bamboo craftsmen. The majority of the population of Muntuk Hamlet work as wood craftsmen (furniture) and bamboo (woven) craftsmen. However, there are also those who work as farmers and traders, but that is only a side job because their main job is wood and bamboo craftsman. The people of Muntuk Village, the majority of whom work as wood craftsmen (meuble) and bamboo craftsmen (anyman) have problems, namely the lack of knowledge and understanding and access to promote these handicraft products using social media, resulting in less than optimal sales and the community's income does not develop. To overcome this, the local government can increase the entrepreneurial potential of the Muntuk Village community through micro and cultural policies, providing facilities, providing education and knowledge to the community in collaboration with surrounding campuses. The government also needs to pay attention to entrepreneurs so that they can use social media as a marketing medium so that they can expand the market more broadly which will ultimately help the economy of the Muntuk Village community.